(untitled) (Revista de Investigaciones Universidad del Quindío, 2020)
The purpose of this research is identified the strategies of reading promotion that are implemented in relation to the criteria in the” Manifesto UNESCO / IFLA school library, in libraries schools of the public educational institutions owned to ‘Quimbaya” commune, located in Armenia. Since right now is critical to the Ministry of National Education, restart and give value to school libraries from their Institutional Education Proyect. This quantitative research was done by conducting surveys, interviews and direct observation, aims to provide an academic contribution from the Science Information and Documentation, Library and Archives of the University of Quindío, identifying training processes that make reading libraries of educational institutions that have school libraries.The results indicate that the school library of these institutions is not exercising the role of being a real agent promoting reading because of the lack of coordination between the PEI and the school library, the absence of clear management policies, characteristics thereof, and a professional in information Science. It is fundamental to create awareness among managers to include the library as a strategic institutional training.